2009
DOI: 10.1371/journal.pgen.1000590
|View full text |Cite|
|
Sign up to set email alerts
|

A Computational Screen for Regulators of Oxidative Phosphorylation Implicates SLIRP in Mitochondrial RNA Homeostasis

Abstract: The human oxidative phosphorylation (OxPhos) system consists of approximately 90 proteins encoded by nuclear and mitochondrial genomes and serves as the primary cellular pathway for ATP biosynthesis. While the core protein machinery for OxPhos is well characterized, many of its assembly, maturation, and regulatory factors remain unknown. We exploited the tight transcriptional control of the genes encoding the core OxPhos machinery to identify novel regulators. We developed a computational procedure, which we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
158
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 69 publications
7
158
0
Order By: Relevance
“…2a), and elevated on average eightfold in primary and sevenfold in PDX tumours (Table 1). CHCHD2 promotes cell migration and regulates oxidative phosphorylation both at the protein level in mitochondria and transcriptionally [30][31][32][33] . Therefore, elevated expression of CHCHD2 may contribute to increased mitochondrial function and cell motility in NSCLC 34 .…”
Section: Articlementioning
confidence: 99%
“…2a), and elevated on average eightfold in primary and sevenfold in PDX tumours (Table 1). CHCHD2 promotes cell migration and regulates oxidative phosphorylation both at the protein level in mitochondria and transcriptionally [30][31][32][33] . Therefore, elevated expression of CHCHD2 may contribute to increased mitochondrial function and cell motility in NSCLC 34 .…”
Section: Articlementioning
confidence: 99%
“…CHCHD10 and its 243 paralogue CHCHD2, which are encoded by genes localized on chromosomes 22q11.23 and 244 7p11.2, respectively, have emerged as a result of gene duplication during the evolution from 245 yeast to man [49]. Human CHCHD2 is essential for optimal respiratory activity [100][101][102], in 246 particular that of CIV [100,102]. CHCHD2 depletion reduces the expression of the mtDNA-247 encoded COX2 subunit of CIV [100].…”
mentioning
confidence: 99%
“…Human CHCHD2 is essential for optimal respiratory activity [100][101][102], in 246 particular that of CIV [100,102]. CHCHD2 depletion reduces the expression of the mtDNA-247 encoded COX2 subunit of CIV [100]. Indeed, bioinformatic analyses of natural variations in 248 human gene expression suggest that CHCHD2 is implicated in the mitochondrial protein 249 translation [103].…”
mentioning
confidence: 99%
“…As it is reported that knockdown of SLIRP 24,25 decreases mitochondrial mRNA levels, 20 we determined the effect of bcl-2 overexpression on the levels of seven transcripts, representative of mitochondrial mRNA and part of respiratory chain complexes I, III, IV and V. As reported in Figure 5a, a significant increment of the levels of cytochrome b (CYTB), cytochrome c oxidase (COX1), NADH-ubiquinone oxidoreductase chain 1 Figure 5g, in bcl-2-overexpressing cells, an increment of SLIRP protein level, not associated to a significant modulation of its transcript (Figures 5a and b), was observed.…”
Section: Resultsmentioning
confidence: 88%
“…20,29 In silico screen for assembly, maturation and regulatory factors of oxidative phosphorylation machine identified SLIRP as player of mitochondrial RNA homeostasis and the mechanism of SLIRP regulation of mitochondrial encoded mRNA has been characterized. 24 SLIRP is part of a ribonucleoprotein complex that regulates posttranscriptional gene expression in mitochondria. 29 In this contest, SLIRP interacts with LRPPRC and knockdown of either SLIRP 24 or LRPPRC 25 results in similar decreases in mitochondrial mRNA levels, indicating that the LRPPRC/SLIRP complex has a specific role in mRNA maturation or stabilization after transcription in mitochondria.…”
Section: Discussionmentioning
confidence: 99%